RNA sequencing of sarcomas with simple karyotypes: identification and enrichment of fusion transcripts - Hofvander, Jakob; Tayebwa, Johnbosco; Nilsson, Jenny; Magnusson, Linda; Brosjö, Otte; Larsson, Olle; Vult von Steyern, Fredrik; Domanski, Henryk A.; Mandahl, Nils; Mertens, Fredrik (Laboratory Investigation, 2015)
Gene fusions are neoplasia-associated mutations arising from structural chromosomal rearrangements. They have a strong impact on tumor development and constitute important diagnostic markers. Malignant soft tissue tumors (sarcomas) constitute a heterogeneous group of neoplasms with 450 distinct subtypes, each of which is rare. In addition, there is considerable morphologic overlap between sarcomas and benign lesions. Several subtypes display distinct gene fusions, serving as excellent biomarkers. The development of methods for deep sequencing of the complete transcriptome (RNA-Seq) has substantially improved the possibilities for detecting gene fusions. With the aim of identifying new gene fusions of biological and clinical relevance, eight sarcomas with simple karyotypes, ie, only one or a few structural rearrangements, were subjected to massively parallel paired-end sequencing of mRNA. Three different algorithms were used to identify fusion transcripts from RNA-Seq data. Three novel (KIAA2026-NUDT11, CCBL1-ARL1, and AFF3-PHF1) and two previously known fusions (FUS-CREB3L2 and HAS2-PLAG1) were found and could be verified by other methods. These findings show that RNA-Seq is a powerful tool for detecting gene fusions in sarcomas but also suggest that it is advisable to use more than one algorithm to analyze the output data as only two of the confirmed fusions were reported by more than one of the gene fusion detection software programs. For all of the confirmed gene fusions, at least one of the genes mapped to a chromosome band implicated by the karyotype, suggesting that sarcomas with simple karyotypes constitute an excellent resource for identifying novel gene fusions.
Keywords: RNA sequencing; Sarcomas; Karyotypes; Fusion transcripts